Behavior for Large Time of a Two-Component Chain of Harmonic Oscillators - Dudnikova, T.V. (Russian journal of mathematical physics, 2018)
We consider a model consisting of two semi-infinite chains of harmonic oscillators with a special particle subject to a harmonic external potential.We study the Cauchy problem for this model. The main goal is to derive the dispersive bounds for the solutions in the energy weighted norms.